571. "Real world" Impact of Letermovir for Prevention of Cytomegalovirus Infection in Hematopoietic-Cell Transplantation. (31st December 2020) - Loecher, Alyssa M; Yum, Kendra; Park, Daniel; Kim, Sara; Saunders-Hao, Patricia; Jakubowski, Rita; Keyzner, Alla; Steinberg, Amir; Rana, Meenakshi; Jacobs, Samantha E
Abstract: Background: Letermovir (LTM) was FDA-approved in 2017 for cytomegalovirus (CMV) prophylaxis in allogeneic hematopoietic cell transplant (HCT) patients. We evaluated the "real-world" impact of LTM in adult HCT recipients at the Mount Sinai Hospital in New York following addition of LTM to our formulary in June 2018. Methods: In this retrospective study, we compared 31 consecutive allogeneic HCT recipients from June 2018-June 2019 who received LTM prophylaxis from Day +10–100 to 36 consecutive CMV-seropositive patients who underwent allogeneic HCT June 2017-June 2018 and did not receive LTM. Clinical and laboratory data were abstracted from the existing electronic medical record. The primary outcome was development of clinically significant CMV infection (CS-CMV) through 6 months post-HCT, defined as CMV viremia or disease requiring antiviral therapy. Results: There were no baseline differences in patient demographics or transplant characteristics between patients who did and did not receive LTM prophylaxis. The median duration of LTM prophylaxis was 96 days (IQR, 66–116). At 6-months post-HCT, the cumulative incidence of CS-CMV was lower in patients receiving LTM prophylaxis vs no prophylaxis (29% vs 61%, respectively; p=0.004, Figure 1). Patients who received LTM developed CS-CMV at a later time post-HCT than those who did not receive prophylaxis (median 160 vs 39 days, respectively; p < 0.01). Among patients with CS-CMV, the median duration of antiviral therapy was 39 vs 70 days in the LTM prophylaxis vs no prophylaxis groups, respectively (p< 0.01). While there was no difference in the incidence of graft-versus-host disease (GVHD), the median time to GVHD diagnosis was longer in the LTM group (63 days vs 27 days in the no prophylaxis group; p=0.02). Between patients who did and did not receive LTM prophylaxis no statistically significant difference was observed, respectively, in incidence of CMV disease (3% vs 14%), hospital re-admission (68% vs 67%), or mortality (26% vs 14%) at 6 months post-HCT. Conclusion: We demonstrated the "real-world" utility of LTM for CMV prevention in HCT recipients. Future studies should further evaluate the impact of LTM on antiviral drug usage, GVHD, and other transplant-related outcomes in this population. Disclosures: All Authors : No reported disclosures